Premature infants born at <25 weeks of gestation may be compromised by currently recommended resuscitation techniques - Lamberska, Tereza; Luksova, Marketa; Smisek, Jan; Vankova, Jana; Plavka, Richard (Acta paediatrica (Oslo, Norway, 2016)
AIM: Standard resuscitation guidelines are based on data from a range of gestational ages. We sought to evaluate the effectiveness of our delivery room resuscitation protocol across a range of gestational ages in preterm infants born at <29 weeks. METHODS: We performed an observational study of prospectively collected video recordings of 73 preterm infants. The percentage of bradycardic patients, time to reach target oxygen saturation and the extent of all interventions were compared between three gestational age groups: 22-24 weeks (n = 22), 25-26 weeks (n = 27) and 27-28 weeks (n = 24). RESULTS: Although the same resuscitation protocol was followed for all infants, bradycardic infants born <25 weeks responded poorly and required significantly longer to reach oxygen saturation targets of >70%, >80% and >90% (p < 0.03). They required significantly more interventions and had higher rate of death (p < 0.05) and severe intraventricular haemorrhage (p < 0.03). Significantly lower heart rate and oxygen saturation values were found in infants with intraventricular haemorrhage. CONCLUSION: Current recommendations for resuscitation may fail to achieve timely lung aeration in infants born at the borderline of viability, leading to higher mortality and morbidity. Sustained inflation and delayed cord clamping may be effective alternatives.
Keywords: Lung aeration; Delivery room stabilisation; Female; novorozenec; Humans; Extremely low gestational age newborns; Male; ženské pohlaví; Gestational Age; Resuscitation; Intraventricular haemorrhage; resuscitace; lidé; gestační stáří; Prospective Studies; mužské pohlaví; prospektivní studie; Infant, Extremely Premature; novorozenci extrémně nezralí; Infant, Newborn